THE APPLICATION OF PHONICS INSTRUCTION TO IMPROVE ENGLISH VOCABULARY OF GRADE 5 CHINESE STUDENTS - Lu, Fan; Pianchana, Techameth (Academic Journal Phranakhon Rajabhat University, 2024)
The study aimed to: 1) compare Grade 5 students’ English vocabulary before and after using phonics instruction, and 2) investigate the students’ satisfaction with the use of phonics instruction in English vocabulary lessons in Hubei province, China. A cluster random sampling method was employed to select a study sample from two Grade 5 classes in a school located in Hubei province. Quantitative data were collected through a pretest and a post-test, evaluating Grade 5 Chinese students' English vocabulary, and a questionnaire indicating their satisfaction with the use of phonics instruction. Subsequently, the collected data were analyzed using a paired sample t-test and descriptive statistics. The results of the pretest and post-test revealed a significant improvement in students' English vocabulary, as indicated by a notable mean difference of 6.4 points between the pretest score and posttest score. Furthermore, the findings from the questionnaire demonstrated that nearly all participants expressed a high level of satisfaction with the implementation of phonics instruction in English vocabulary lessons. Consequently, this study underscored the effectiveness of phonics instruction as an alternative method for teaching and learning English vocabulary.